2016
DOI: 10.1177/0143831x16669842
|View full text |Cite
|
Sign up to set email alerts
|

The strange non-death of employer and business associations: An analysis of their representativeness and activities in Western European countries

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full DRO policy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
67
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(72 citation statements)
references
References 33 publications
5
67
0
Order By: Relevance
“…EOs' main functions were once to counter trade union power and conduct collective bargaining, but the decline of these institutions raised concerns as to the continued existence of EOs. However, researchers pointed to the “strange non‐death of employer associations” (Brandl & Lehr, ) to debate the continuing relevance of EOs (Ibsen & Navrbjerg, ; Sezer, ). This article contributed to this debate by arguing that EOs adapted to changing socio‐economic contexts by evolving within and across three roles—as an IR actor, a political actor and a service provider.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…EOs' main functions were once to counter trade union power and conduct collective bargaining, but the decline of these institutions raised concerns as to the continued existence of EOs. However, researchers pointed to the “strange non‐death of employer associations” (Brandl & Lehr, ) to debate the continuing relevance of EOs (Ibsen & Navrbjerg, ; Sezer, ). This article contributed to this debate by arguing that EOs adapted to changing socio‐economic contexts by evolving within and across three roles—as an IR actor, a political actor and a service provider.…”
Section: Resultsmentioning
confidence: 99%
“…As we discuss in this article, employer collective organisation was hampered by broader developments such as declining government support for collective regulation and economic governance, weakening of labour unions, the liberalisation of markets, and, economic internationalisation. However, the ‘strange non‐death of employer associations’ (Brandl & Lehr, ) meant that EOs survived despite adverse conditions by evolving in their roles as IR actor, political actor and service provider to maintain relevance to their members.…”
Section: Introductionmentioning
confidence: 99%
“…It is likely that within coordinated market economies negotiating EOs comprise a larger share of the total population (Martin and Swank, 2012;Ibsen, 2016) EOs and labour unions have been impacted by similar changes such as changing government regulation and the internationalization of the economy (Brandl and Lehr, 2016). However, employment relations research has to a far greater extent focussed on labour unions, neglecting the examination of EOs.…”
Section: Resultsmentioning
confidence: 99%
“…EO were a neglected subject within the employment relations literature (Barry and Wilkinson, 2011;Brandl and Lehr, 2016). Much of this neglect was attributable to the conflation of employer collective action with collective bargaining.…”
Section: Explaining Employer Collective Actionmentioning
confidence: 99%
“…al, 2016;You and Barry, 2016;Zhu and Leyland, 2017;Gooberman, Hauptmeier and Heery, 2017, 2018, 2019a, 2019b demonstrated that employer collective organizations continue to thrive in countries featuring different institutional characteristics. These and other studies ensured that the 'strange non-death of employer and business associations' (Brandl and Lehr, 2016) emerged as a focus of study within employment relations.…”
Section: Introductionmentioning
confidence: 99%